UMP’s Joyous ‘1Malaysia’ Light Festival Night - UMP, PNC
More than 1,000 people including students from institutes of higher learning and local residents in Kuantan flocked Universiti Malaysia Pahang (UMP) Sports Complex to celebrate the Light Festival Night organised by the university’s Cultural and Arts Club on Oct 18, 2010.